PENGARUH WUDHU TERHADAP KEJADIAN INSOMNIA PADA LANSIA DI PANTI SOSIAL TRESNA WERDAH (PSTW) BERINGIN KABUPATEN GORONTALO - Pipin Yunus; Apris Tilome (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The aim of this reseach was to know the effecting of abulation about incidence of insomnia on elderly in social rehabilition of Tresna Werdha (PSTW) at Gorontalo city. Design of research used Quasi Experiment with design of Non Equivalent control group pre - post test. Taken of sample through accidental sampling with the total 30 respondent that used statical test paired samples T-tes. The result of this research showed that on experiment group has effecting of abulation about incidence of insomnia on elderly that found the significant value in the beginning and the end P = 0.000 ≤ α 0,05 while the control group there not has ablution effecting on incidence of insomniain elderly got the significant value at the beginning of the meeting P = 0.334 ≥ α 0.05 and the end of the meeting of P = 0.054 ≥ α = 0.05.